The Development of a Practicum Learning Module to Enhance Competence in Car Air Conditioning Maintenance at SMK Al Asror Semarang - Masyrifah, Marham Ab Lathif Azzaky; Burhan Rubai Wijaya; Noor Hudallah (Jurnal Profesi Keguruan, 2025)
This study aims to improve the automotive air conditioning (AC) maintenance competency of students at SMK Al Asror, in the Heating, Ventilation, Air Conditioning, and Refrigeration (HVACR) vocational program. The research method employed is a development research approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. In the analysis phase, the researcher identified a lack of facilities and infrastructure as a key factor contributing to students’ low competency scores. During the design phase, a maintenance module was developed based on the Indonesian National Work Competency Standards (SKKNI). The development phase involved validation testing by subject matter experts and media experts, who provided input for revisions. This study was conducted at SMK Al Asror Semarang, with a total population of 29 students, all of whom were used as the research sample. A pre-vocational competency test (pretest) was conducted before the intervention, followed by a posttest after the intervention. The practicality of the module was also analyzed based on aspects such as ease of use, clarity, design, usefulness, and relevance. In the final evaluation stage, a practical competency test in automotive AC maintenance was conducted with external assessors from industry partners. The findings indicate that the use of the maintenance module is effective in enhancing students' competency in automotive AC maintenance.